The landmark series: desmoid : continuing education - sarcoma - Fiore, Marco; Crago, Aimee; Gladdy, Rebecca; Kasper, Bernd (Annals of surgical oncology, 2021)
Desmoid-type fibromatosis represents a challenge in the landscape of surgical oncology, for several reasons. The tumors can be infiltrative and locally aggressive, surgery may be morbid, and patients are usually young, and thus treatment sequelae must be managed for decades. Desmoids do not have metastatic potential, therefore management strategies for desmoids have evolved to employ frontline treatments that are largely non-operative. In fact, with unpredictable and benign behavior, we now recognize that desmoids can also stabilize and regress, making active observation an option for many patients. Moreover, many medical therapies are active in the disease. We reviewed landmark studies describing contemporary issues that affect treatment recommendations for desmoid patients: prognostic factors, indication to active surveillance, role of surgical margins, postoperative radiotherapy, and the most recent expert consensus papers.
Gesehen am 19.08.2021